2009
DOI: 10.1158/1078-0432.ccr-08-1860
|View full text |Cite
|
Sign up to set email alerts
|

Multi-center, Placebo-controlled, Double-blind, Randomized Study of Oral Toceranib Phosphate (SU11654), a Receptor Tyrosine Kinase Inhibitor, for the Treatment of Dogs with Recurrent (Either Local or Distant) Mast Cell Tumor Following Surgical Excision

Abstract: Purpose: The purpose of this study was to determine the objective response rate (ORR) following treatment of canine mast cell tumors (MCT) with toceranib phosphate (Palladia, SU11654), a kinase inhibitor with both antitumor and antiangiogenic activity through inhibition of KIT, vascular endothelial growth factor receptor 2, and PDGFRβ. Secondary objectives were to determine biological response rate, time to tumor progression, duration of objective response, health-related quality of life, and safety of Pall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
426
6
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(478 citation statements)
references
References 47 publications
(54 reference statements)
22
426
6
9
Order By: Relevance
“…Metastatic MCT represents a major health problem in the canine population, but the introduction of a novel class of targeted antineoplastic agents directed against KIT, TKI, has significantly changed the therapeutic options available for these dogs 7, 8. Indeed, the important role of targeted therapy against molecules contributing to tumor development, progression, and metastasis has attracted considerable attention 31…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic MCT represents a major health problem in the canine population, but the introduction of a novel class of targeted antineoplastic agents directed against KIT, TKI, has significantly changed the therapeutic options available for these dogs 7, 8. Indeed, the important role of targeted therapy against molecules contributing to tumor development, progression, and metastasis has attracted considerable attention 31…”
Section: Discussionmentioning
confidence: 99%
“…Although TKI‐based therapy is used in dogs with MCT to also treat metastatic disease in the lymph nodes,7 c‐kit status is generally evaluated in the primary lesions because metastatic sites are rarely removed or biopsied before treatment. However, it is still unknown whether c‐kit status differs in metastases compared with primary tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47 This study supports the use of feline SCC as a model for HNSCC, an approach that could potentially benefit both felines and humans alike. During the development of a TKI against KIT (SU11654, toceranib) 48 the human field benefited greatly from the canine studies, 47 and the development of acquired resistance to single-agent TKIs in dogs with mast cell tumors is of particular interest. 47 Further studies in cats with SCCs using EGFR targeting siRNA based therapies in combination with radiotherapy would potentially advance the treatment of the disease in both species.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…The presence of these mutations is associated with higher-grade tumors. 20,29,38 Mutations result in constitutive activation of KIT, initiating signaling cascades leading to proliferation, survival, and invasion. 9,[15][16][17][18]21,22,29 One group reported that the presence of ITD mutations of c-KIT or aberrant cytoplasmic KIT protein localization was significantly associated with higher values of Ki67.…”
mentioning
confidence: 99%